2021
DOI: 10.1016/j.csbj.2021.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Chaos game representation and its applications in bioinformatics

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 65 publications
0
20
0
Order By: Relevance
“…In areas where identification is important, such as identifying the presence of disease vectors, an elevated false-negative or positive rate is unacceptable. We believe that the approach presented here and others (such as one-shot and few-shot learning) have significant potential for being used as a basis for classifying reads from environmental samples since genomic signatures and deepneural networks can capture global patterns within genomes that other approaches may miss 29,34,61 . For example, FCGRs can be seen as more than just k-mer counts since visual information about the overall structure of sequence, along with k-mer counts, is encoded into the representation 29,34,62 .…”
Section: Accessionmentioning
confidence: 99%
See 1 more Smart Citation
“…In areas where identification is important, such as identifying the presence of disease vectors, an elevated false-negative or positive rate is unacceptable. We believe that the approach presented here and others (such as one-shot and few-shot learning) have significant potential for being used as a basis for classifying reads from environmental samples since genomic signatures and deepneural networks can capture global patterns within genomes that other approaches may miss 29,34,61 . For example, FCGRs can be seen as more than just k-mer counts since visual information about the overall structure of sequence, along with k-mer counts, is encoded into the representation 29,34,62 .…”
Section: Accessionmentioning
confidence: 99%
“…Following this, each CR sequence was transformed into a FCGR with a depth of 6 29 . Previous work has shown that this representation has the ability to efficiently summarize the unique characteristics of each genome and can be used for clustering and supervised learning 26,[34][35][36] . The FCGRs for each CR, along with the class labels, were then used as inputs into a semi-supervised deep learning model 27 .…”
Section: Validation Against Non-culicidae Dipteran Mitogenomesmentioning
confidence: 99%
“…The DNA classification methodology was implemented in this research to generate significant development using comparative processing algorithms with image matrices due to the progress of computational platforms (Hoang et al, 2016). This methodology includes sequencing applications using fractal selfsimilarity theories and chaos game representation (CGR), reporting progress in genetics and protein field applications (Löchel and Heider, 2021;Jones et al, 2011). Spatial activities sequencing data will be mapped in the habitat and the characterization and classification analysis through the typical fractal image matrices of the deterministic spatial behavior of an animal will be implemented using algorithms with low computational cost compared to other methodologies and focused on cattle welfare projection and the rational management of ecosystems (Herlin et al, 2021;Hoang et al, 2016;Wang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the 2-dimensional FCGR representation of the sequences must be flattened and cannot be fully exploited. For an extensive review on CGR and its applications in bioinformatics, we refer the reader to [21].…”
Section: Introductionmentioning
confidence: 99%